Lawsone attenuates acute low dose ethanol-induced skin inflammation in A431 epidermoid carcinoma skin cells and its possible mechanisms in targeting interleukin (IL)-1α in silico - Zulkefle, Hani Syahirah; Abdullah, Shazleen Sofea; Mohammad Latif, Muhammad Alif; Md Tohid, Siti Farah (Life Sciences, Medicine and Biomedicine, 2024)
Standard treatment for acute skin inflammatory conditions comes with unwanted side effects. Traditionally, Lawsonia inermis has been used to treat skin-related ailments, with lawsone as the main active phytochemical is predicted to inhibit a skin pro inflammatory cytokine, IL-1α. This study is aimed to evaluate the anti- inflammatory effect of lawsone in acute ethanol-induced skin inflammatory condition in vitro, by targeting IL-1α in silico. Basically, the IC50 of lawsone on human epidermoid carcinoma cell line (A431) was obtained by using MTT proliferation assay, followed by acute low dose ethanol-induced inflammatory skin condition on A431 cells to determine cell viability. Next, molecular docking study was done by utilizing Autodock Vina software, and further analyzed by ProteinsPlus and PyMol softwares. Meaningful interaction that exist in the binding of lawsone to IL-1α was determined by molecular docking results comparison with two other compounds (kirenol and curcumin diglucoside). In vitro study showed the IC50 of lawsone in low cytotoxicity level at 150 µM. Skin anti-inflammatory assay indicated that lawsone has highly significant (p<0.05) anti-inflammatory activity at 9.375 µM at low concentration, but not effective at higher concentrations (more than 18.75 µM). In silico studies indicated binding of lawsone to IL-1α with top binding affinity of -5.2 kcal/mol, at binding residues of Asp65 and Ile68. Docking comparison analysis to determine meaningful interaction comparison indicated three key IL-1α binding residues common to most tested compounds, such as Ile68 and Asp65 thus supported the predicted mechanistic pathway. This highlighted lawsone potential as a future skin anti-inflammatory agent with minimal toxicity.